ӘЖИНИЯЗ ЛИРИКАСЫНДА ТӘРИЙИПЛИК ШЫҒАРМАЛАР - Давлетов, Б.А. (FAN va JAMIYAT, 2024)
The article analyzes the artistic works of the son of Ajiniyaz Kosiboy, a representative of the 19th century Karakalpak lyricist. Ideological-thematic directions, genre and artistic features of the poet's descriptive works are studied on the example of the texts of the work. In the descriptive songs, the expression of the theme of the birthplace, Motherland, love, and women is revealed.